ارزیابی فرهنگ ایمنی در بندر خرمشهر بر اساس مهندسی رزیلینس - زهرا قاسمی; لیلا ابراهیمی قوام آبادی (Journal of Safety Promotion & Injury Prevention, 2019)
Background and Objectives: ports as the gate of entry and exit of goods have a basic role in the economic progress in developing and developed countries. Compression and complexity of activities in ports have caused these areas to be dangerous with a high rate of vulnerability and high ratio of incidents. Areas which need establishing a suitable standard with the culture-making approach in the aspect of safety and resilience engineering, to minimize damages and to upgrade the safety level in ports, and also preparedness of ports for unpredictable incidents. Martials and Methods: This descriptive and cross-sectional study was conduct on 90 staffs of khormashar port in 2018. Participants were selected randomly and voluntarily participated in the study. Data was collected by a standard safety culture questionnaire. The collected data has been analyzed by using Single sample t test, Kolmogorov- Smirnov test, and Friedman ranking test. Results: Six factors affecting the safety culture were identified which include: management commitment, transparency, learning culture, preparedness, flexibility, and knowledge. Results showed that management commitment (4.69) and knowledge (2.61) had the most and the least importance, respectively. Conclusion: for improvement of resilience and safety culture, one can focus on affective factors based on priority, and take action in the way of supervision and improving them. Modification and improvement of these indicators would lead to the progress in safety and resilience level and will facilitate the movement of this port in the way of reaching higher levels of safety.